Social cohesion, Twitter and far-right politics in Australia: Diversity in the democratic mediasphere. (October 2019) - Lewis, Jeffrey; Pond, Philip; Cameron, Robin; Lewis, Belinda
The concept of 'social cohesion' has become an orthodoxy in governmental and academic discourse, augmenting the complex of progressive and liberal politics that have formed around the modern, multicultural and globally engaged nation-state. The reinvigoration of far-right politics is challenging this orthodoxy, at least inasmuch as these politics appear to be gaining traction through the strategic manipulation of increasing insecurity within these democratic states. This article examines these challenges conceptually and through an empirical case study. The case study examines the appearance in 2016 of Senator Elect Pauline Hanson on the ABC's Q&A television programme. The article examines Twitter discourses that were generated around the far-right senator's appearance on the broadcast programme. The article concludes that 'social cohesion' and its role in electoral, participative and deliberative democratic processes is a largely inadequate discursive buttress to the complex of language wars within which the concept is besieged.